2013
DOI: 10.1165/rcmb.2012-0454oc
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-Activatable Fibrinolysis Inhibitor Protects against Acute Lung Injury by Inhibiting the Complement System

Abstract: Acute lung injury (ALI) is a devastating disease with an overall mortality rate of 30 to 40%. The coagulation/fibrinolysis system is implicated in the pathogenesis of ALI. Thrombin-activatable fibronolysis inhibitor (TAFI) is an important component of the fibrinolysis system. Recent studies have shown that the active form of TAFI can also regulate inflammatory responses by its ability to inhibit complement C3a, C5a, and osteopontin. We hypothesized that TAFI might have a protective role in ALI. To demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…Mice deficient in TAFI are protected against vascular remodeling in the lung associated with pulmonary hypertension (20). During LPS-induced acute lung injury, TAFI has been shown to be protective, possibly by regulation of the complement pathway (21). However, in a model of abdominal sepsis, TAFI-deficient mice did not show any decrease in fibrin accumulation in the lung (22).…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient in TAFI are protected against vascular remodeling in the lung associated with pulmonary hypertension (20). During LPS-induced acute lung injury, TAFI has been shown to be protective, possibly by regulation of the complement pathway (21). However, in a model of abdominal sepsis, TAFI-deficient mice did not show any decrease in fibrin accumulation in the lung (22).…”
Section: Discussionmentioning
confidence: 99%
“…In acute lung injury caused by instillation of LPS, Cpb2 − / − mice had exacerbated disease as compared with WT mice . The use of a C5a receptor antagonist demonstrated that CPB2 protected against injury via inactivation of C5a.…”
Section: Roles For Cpb2 Explored In Cpb2−/− Micementioning
confidence: 99%
“…The acute inflammatory condition of the pancreas is often subsequent to infectious attacks that may consequently result in multisystem organ dysfunction, including that of acute lung injury (ALI) . The incidence of ALI in cases of AP remains a complex medical issue, which is associated with high rates of mortality ranging from 30% to 40% . ALI occurrence in patients with severe AP exhibits significant variations often depending on predisposing factors, which often dictate outcomes and poor prognoses in an independent fashion .…”
Section: Introductionmentioning
confidence: 99%